A Collaboration Journey towards Unlocking Indonesia's Literacy - Arif Maspul, Kurniawan (Banun: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
ABSTRACT Literacy has emerged as a critical pillar for societal growth in Indonesia's ever-changing educational scene. The study examines Indonesia's comprehensive approach to literacy promotion, taking into account cultural, psychological, and policy elements. It is vital to disentangle the complex kaleidoscope of influences producing Indonesia's literacy environment utilizing sociocultural studies, educational psychology, language analysis, and policy formulation as lenses. From cultural norms that influence reading habits to the psychological complexities of literacy development, each component provides insights into the problems and potential of cultivating a literate society. Addressing these challenges and releasing literacy's revolutionary power will need collaborative actions combining government, education, communities, and the commercial sector. The article combines theoretical insights, empirical evidence, and practical strategies, emphasizing literacy's critical role in driving socioeconomic development and promoting inclusive progress. As people continue on this collaborative journey to unlock Indonesia's literacy potential, the question comes up: Why does it matter? Keywords: Metacognitive Strategies, Critical Pedagogy, Sociocultural Theory, Collaborative Partnerships, Evidence-Based Interventions